Narrar a voz: trajetórias de uma voz-experiência em busca da voz própria - Gelamo, Renata Pelloso [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In this thesis, I present questions, reflections, and learnings from narratives, either mine and form other people which whom I met during the trajectories in the search for the self-voice and that led me to the creation of the “Voice Atelier”, a project built in the borderline of different fields of knowledge which hold the voice as its interest. The textual structure I propose for this thesis shows the creation and sustaining of a space where I could name, in first person, the processes I lived during my own history with the voice. I narrate moments of impoverishment of the experience, passing through the silencing of my own voice, submitted to what others had to say, or about what the renowned scientific fields had to say about the voice, as well as the experience of collapse lived through the contact wit the voices of the working songs of the Destaladeiras de Fumo (Workers who manually struke tobacco leafs) from Arapiraca, when I suspended all the truths I knew by then about the voice. At last, I narrate how the “Voice Atelier” happens, an opens space for invention of a voice-experience, a voice that can listen and be listened, can narrate its own history, inhabits its own body and, exposes, looks after and is aware of itself. Through this pathway of the voice-experience we reach the self-voice: A voice capable of self-enunciating and self-inventing.

Neste trabalho, apresento questões, reflexões e aprendizados a partir de narrativas, minhas e de outras pessoas, com as quais me encontrei durante as trajetórias em busca de uma voz própria e que me levaram à criação do Ateliê de Voz, um projeto constituído nas fronteiras de diferentes áreas do conhecimento que tem a voz como interesse. A estrutura textual que propus para este trabalho mostra a criação e a sustentação de um espaço onde pude nomear, em primeira pessoa, os processos que vivi durante a minha história com a voz. Narro momentos de empobrecimento da experiência, passando pelo silenciamento da minha voz, submetida ao que os outros tinham a dizer ou ao que as áreas consagradas da ciência tinham a dizer à respeito da voz, assim como a experiência de tombamento vivida no contato com as vozes dos cantos de trabalho das Destaladeiras de Fumo de Arapiraca, em que coloco em suspensão todas as verdades sobre a voz até então conhecidas por mim. Por fim, narro como acontece o Ateliê de Voz, um espaço em aberto para a invenção de uma voz-experiência, uma voz que escuta e pode ser escutada, pode narrar a própria história, habita o próprio corpo e se expõe, cuida de si e se percebe. Por esse caminho da voz-experiência chegamos à voz própria: uma voz pode enunciar a si próprio e inventar a si próprio.
Narrating the voice: trajectories of a voice-experience in a search of the self-voice
Keywords: Experiência; Voz própria; Voz-experiência; Narrativa; Experience; Self-voice; Voice-experience; Narrative